Orthodox and modern: studies in the theology of Karl Barth - McCormack, Bruce L. (Baker Academic, 2008)
Introduction -- Karl Barth's relationship to nineteenth-century theology -- Revelation and history in transfoundationalist perspective : Karl Barth's theological epistemology in conversation with a Schleiermacherian tradition -- The sum of the Gospel : the doctrine of election in the theologies of Alexander Schweizer and Karl Barth -- What has Basel to do with Berlin? : continuities in the theologies of Barth and Schleiermacher -- The significance of Karl Barth's theological exegesis of Philippians -- Karl Barth's relationship to postliberalism and postmodernism -- Beyond nonfoundational and postmodern readings of Barth : critically realistic dialectical theology -- "The limits of the knowledge of God" : theses on the theological epistemology of Karl Barth -- Karl Barth's theological ontology -- Grace and being : the role of God's gracious election in Karl Barth's theological ontology -- Karl Barth's historicized christology : just how "chalcedonian" is it? -- Participation in God, yes, deification, no : two modern Protestant responses to an ancient question -- Seek God where he may be found : a response to Edwin Chr. van Driel occasional writings -- The Barth renaissance in America : an opinion -- Theology and science : Karl Barth's contribution to an ongoing debate -- Foreword to the German edition of Karl Barth's critically realistic dialectical theology -- Review of Johann Friedrich Lohmann's Karl Barth und der Neukantianismus -- Review of Karl Barth's the Holy Spirit and the Christian life